1995
DOI: 10.1017/s0031182000064829
|View full text |Cite
|
Sign up to set email alerts
|

Ecological, morphological and genetic characterization of sympatric Haemonchus spp. parasites of domestic ruminants in Mauritania

Abstract: The 4 species of ruminants (dromedary, zebu cattle, sheep and goat) in arid areas of Mauritania harboured Haemonchus spp. as the most frequent internal parasite. This was a rare situation where the 3 putative species, H. longistipes (dromedary), H. placei (zebu cattle) and H. contortus (sheep and goat) occurred sympatrically. The study was undertaken on hosts slaughtered at the Nouakchott abattoir, on the basis of monthly collection of worms. The environment was very unfavourable to H. placei and unfavourable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…in goats (15.5 %) suggesting that small ruminants are most susceptible and usual host of H. contortus than H. longistipes. This result supports the work of Achi et al (2003), Gelaye & Abebe (2001), Jacutet et al (1992, 1995, Thomas et al (2007) all of which reported the dominance of H. contortus in small ruminants. Additionally, the present study also imply that goats could also host H. longistipes, which was reported for the first time infecting goats at upper Egypt region; and it is in agreement with previous studies conducted by Jacutet et al (1992).…”
Section: Morphological Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…in goats (15.5 %) suggesting that small ruminants are most susceptible and usual host of H. contortus than H. longistipes. This result supports the work of Achi et al (2003), Gelaye & Abebe (2001), Jacutet et al (1992, 1995, Thomas et al (2007) all of which reported the dominance of H. contortus in small ruminants. Additionally, the present study also imply that goats could also host H. longistipes, which was reported for the first time infecting goats at upper Egypt region; and it is in agreement with previous studies conducted by Jacutet et al (1992).…”
Section: Morphological Resultssupporting
confidence: 90%
“…Regarding to Haemonchus species identification were performed according to descriptions of Jacquiet (1995). Data were presented in tables.…”
Section: Parasitological Examinationmentioning
confidence: 99%
“…Tod (1965) also considered that vulvar morphology is a manifestation of some genetic factors important to establish and develop in hosts. Vulvar morphology is also considered as markers of ecological adaptation to an area (Rose, 1966;Le Jambre & Whitlock, 1968;Jacquiet, 1995). These investigators described that, based on vulvar morphology, it is possible to arrange Haemonchus spp.…”
Section: Vulvar Morphologymentioning
confidence: 99%
“…Haemonchus represent the most economically important helminth parasites in cattle, sheep, and goats throughout the world (Gibbs and Herd, 1986), and considerable research has been conducted on those species, H. contortus (Rudolphi, 1803), H. placei (Place, 1893), and H. similis, Travassos, 1914, that are globally distributed in domesticated Bovinae and Caprinae. Another 7 species, H. bedfordi Le Roux, 1929, H. dinniki Sachs, Gibbons and Lweno, 1973, H. horaki Lichtenfels, Pilitt, Gibbons and Boomker, 2001, H. krugeri Ortlepp, 1964, H. lawrencei Sandground, 1933, H. mitchelli Le Roux, 1929, and H. vegliai Le Roux, 1929, are primary parasites among respective host groups and species of wild Bovinae, Cephalophinae, Reduncinae, Aepycerotinae, Antilopinae, Alcelaphinae, and Caprinae in sub-Saharan Africa, whereas H. okapiae van den Berghe, 1937 occurs in Giraffidae, and H. longistipes Railliet and Henry, 1909 occurs in Camelidae and domestic sheep, goats, and rarely, cattle across a broader range extending from Africa to southern Eurasia (Gibbons, 1979;Jacquiet et al, 1995;Lichtenfels et al, 2001Lichtenfels et al, , 2002. Although as a group these nematodes have been the focus of considerable taxonomic study, there has been no previous attempt to elucidate phylogenetic relationships among the recognized species of Haemonchus (e.g., Almeida, 1935;Gibbons, 1979).…”
mentioning
confidence: 99%